Optical Beat Interference in Optical Communication System - Al-Qdah, Malik Taysir (2006)
Subcarrier Multiplexing (SCM) can be used to increase the capacity of any optical network. Both Single-Optical-Carrier (SOC) and Multiple- Optical-Carrier (MOC) SCM systems can be employed. However, in SCMMOC systems, when two lasers carrying subcarrier channels operate with very close spaced wavelength, beating between the lasers and beating between the lasers and Four-Wave Mixing (FWM) terms can occur. This will increase the noise at the photodetector. This type of noise is called Optical Beat Interference (OBI) and it is dependent on the accumulated Chromatic Dispersion (CD) experienced transmission. This thesis establishes a new approach to reduce OBI by suppressing the optical carrier. The effect of OBI in the presence of FWM is also examined and analyzed. Additionally, applications of OBI in optical communications are investigated, particularly for measuring CD and the modulator frequency chirp.The new approach for OBI reduction uses optical carrier suppression. This method achieved a 28 dB improvement in the Carrier-To- Interference (CIR) ratio. In addition, OBI penalty in SCM-MOC network in the presence of FWM is studied mathematically and verified through a simulation exercise, which shows that the maximum number of subcarrier or the bandwidth of the SCM-MOC system will be limited by Main-Beating and FWM-Beating when FWM is present. The novel technique for CD measurement is performed by simultaneously launching a pump and probe optical signals at ol angular optical frequency separation, and two phase-conjugated terms into the SMF. The relative power of the beat frequencies that appear after the photodetector at 01 and at 201 is used to determine the accumulated CD. This technique was successfully demonstrated using a Semiconductor Optical Amplifier (SOA) as a phase conjugator to achieve a 19 dB relative power variation as a result of up to 1900 ps/nm CD change. A new method to measure the modulator frequency chirp parameter using OBI is performed in two steps. In the first step, the frequency separation between two optical signals passing through a phase conjugator is changed, produces a resonance reference frequency as a result of the accumulated fiber CD. In the second step, an RF modulated signal passes through the same length of fiber as in the first step. A second resonance frequency is produced as a result of fiber CD and modulator chirp. The difference between the two resonance frequencies is used to measure the modulator chirp. The new method achieves a measurement range of * 5 and maximum resonant frequency of 8.1 GHz at an accumulated CD 1632 ps/nm.